Palgrave dictionary of emerging markets and transition economics - Holscher, Jens; Tomann, Horst (Palgrave Macmillan, 2015)
"The period of transition from socialism to capitalism in parts of Europe and Asia over the past 25 years has attracted considerable interest in academia and beyond. From the Editors of Palgrave's iconic series 'Studies in Economic Transition' comes the Palgrave Dictionary of Emerging Markets and Transition Economics. This dictionary addresses the needs of students, lecturers and the interested general public to quickly find definitions and explanations of topics, institutions, personalities and processes in this historical phase of changing societies, which as such is not concluded. Today newly emerging market economies try to learn from experiences made by transition economies. Those who love The New Palgrave Dictionary of Economics will enjoy the format in this Dictionary, which uses an encyclopedia-based approach where articles not only define the terms but provide an overview of the evolution of the term or theory and also touch on the current debates"--